Epidemiological and clinical characteristics of mpox: a retrospective study in Lima, Peru - Reaño Tovar, Fernando Manuel (2024)
The World Health Organization (WHO) began to receive reports of mpox (monkeypox) cases from non-endemic countries in 2022. In Peru, the number of cases increased to the point where it ranked among the top 10 countries in the world with the most confirmed cases. The objective of this study was to determine the clinical and epidemiological characteristics of patients with a confirmed diagnosis of mpox treated at a hospital in Lima from July to December 2022. A total of 124 cases were confirmed with molecular testing. The mean age was 34 years. The vast majority of reported mpox cases have been among males, men who have sex with men, homosexuals and people with HIV. Moreover, the majority of people with HIV were receiving antiretroviral treatment at the time of diagnosis. The exanthem prevailed as a clinical manifestation, followed by fever, headache and chills. The most common skin lesion was crust/scab (83.06 %) and most patients (98.39 %) did not require hospitalization. No deaths were reported in this study. It is necessary to educate the population in preventive actions, especially aimed at the most affected individuals. Additionally, eliminating stigmas will contribute to its early detection and control of the disease in future outbreaks.